Turbidity Removal from Kaolin Synthetic Wastewater via Coagulation Process Using Sludge from Water Treatment Plant - Zainol, Noor Ainee; Khalilullah, Putri Al Balqis; Abdul Ghani, Azlinda; Abdul Rashid, Najihah; Mohd Zaini Makhtar, Salwa (International Journal of Integrated Engineering, 2022)
This study aims to treat kaolin synthetic wastewater by using sludge from water treatment plant as a coagulant via the coagulation process. Water treatment sludge (WTS) was characterized by using Fourier transform infrared (FTIR), Scanning electron microscope (SEM), and X-ray diffraction (XRD). WTS had an amorphous structure and contained high aluminium metal constituents at 25.3%, which can be recovered as a coagulant. Acidification was conducted to recover the aluminium in WTS using sulphuric acid and produced water treatment sludge coagulant (WTSC). The optimum condition of WTSC prepared from WTS was evaluated through sludge concentration and acid dosage parameters. It has been observed that 0.5% sludge concentration acidified with 0.08 ml/ml sulphuric acid and normality constant at 0.5N was the optimum condition as it can remove turbidity at 99.5%. The performance of WTSC in the coagulation process using a standard jar test was studied based on the effect of pH and dosage of coagulant. The highest percentage turbidity removal (98.66%) was obtained at pH 12, kaolin turbidity was 117NTU, and WTSC dosage at 40mg/L. The percentage turbidity removal for alum and WTSC was almost similar. Thus, WTSC can potentially replace alum as a coagulant in water treatment plant (WTP).